2011
DOI: 10.5367/ihe.2011.0056
|View full text |Cite
|
Sign up to set email alerts
|

Changing Struggles for Relevance in Eight Fields of Natural Science

Abstract: This paper investigates the consequences of institutional changes on academic research practices in eight fields of natural science in the Netherlands. The authors analyse the similarities and differences among the dynamics of these different fields and reflect on possible explanations for the changes observed. The study shows that the increasing pressure for productivity, as measured in bibliometric terms, can counteract the pressure for practical utility. Moreover, the work indicates that the dynami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 26 publications
(23 reference statements)
0
9
0
Order By: Relevance
“…For example, Chavarro et al [ 55 ] found that locally relevant knowledge in a developing country such as Colombia tends to be associated with distal IDR (higher balance and disparity, lower variety) rather than with proximal IDR. Hessels et al [ 66 , 67 ] have empirically documented across various fields the tensions that researchers focused on societal issues experience against when subject to bibliometric evaluations. One can thus speculate of a lack of alignment between reward incentives in academia (citations) and societal needs or demands [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Chavarro et al [ 55 ] found that locally relevant knowledge in a developing country such as Colombia tends to be associated with distal IDR (higher balance and disparity, lower variety) rather than with proximal IDR. Hessels et al [ 66 , 67 ] have empirically documented across various fields the tensions that researchers focused on societal issues experience against when subject to bibliometric evaluations. One can thus speculate of a lack of alignment between reward incentives in academia (citations) and societal needs or demands [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…While universities (still) dominate the performer side of publicly funded research systems (Frank & Gabler, 2006), mobility and inter-institutional collaborative efforts appear to have increased (Heinze & Kuhlmann, 2008); universities have complemented traditional organizational structures with new cross-departmental entities (Musselin, 2007); funding systems have grown increasingly complex and stimulated both truncation of research efforts in time-limited projects and the formation of new collaborative entities, sometimes with private sector involvement (Braun, 1998; Geiger & Sa, 2008). Academic science has increased its output in terms of growth in the number of publications, and research efforts have become subject to more administration and strategic planning of, for example, grant applications, publishing, outreach, collaboration, and anchoring in various organizational segments and sectors of this increasingly complex system (Deem et al, 2007; Hessels et al, 2011; Leišytė, 2007; Radder, 2010). Generally, it seems individual scientists are exposed to greater complexity and uncertainty and that a significant share of their work is today about strategic maneuvering in complex bureaucracies and fragmented disciplinary landscapes, and (partial) compliance with structures and norms alien to their professional identities (Elzinga, 2012; Schimank, 2005; Weingart, 2005; Ziman, 1994).…”
mentioning
confidence: 99%
“…In particular, researchers mention the benefits of testing the applicability of their research which helps to fine-tune their theories and technologies. In line with this finding, studies have also found that researchers engage with industrial partners to access new or specific forms of (practical) knowledge and expertise (Hessels et al, 2011; Meyer-Krahmer and Schmoch, 1998).…”
Section: Theoretical and Analytical Frameworkmentioning
confidence: 66%